Physical and Chemical Properties, Biosafety Evaluation, and Effects of Nano Natural Deer Bone Meal on Bone Marrow Mesenchymal Stem Cells - Li, Yongbo; Tan, Zhe; Zhang, Jixiang; Mu, Junhan; Wu, Han (Frontiers in Bioengineering and Biotechnology, 2022)
At present, bone-based products are very abundant, and the main sources are bovine bone and pig bone, but there are few studies on the development of deer bone as a bone repair material. Deer bone has important pharmacological effects in the theory of traditional Chinese medicine. It is rich in protein, ossein, a variety of trace elements, with the effect of strengthening tendons and bones. Nanomaterials and their application in the repair of bone defects have become a research hotspot in bone tissue engineering .In this study, nano deer bone meal (nBM), nano calcined deer bone meal (nCBM), nano decalcified bone matrix (nDBM) were successfully prepared. It was found that Ca/P ratio in deer bone was significantly higher than that in cow bone and human bone tissue, and it contained beneficial trace elements, such as potassium, iron, selenium and zinc, which were not found in cow bone. The three kinds of deer bone powder prepared in this study have good biocompatibility and meet the implantation standards of medical biomaterials. Cell function studies showed that compared with other bone powders, due to the presence of organic active ingredients and inorganic calcium and phosphate salts, nBM has excellent performance in the proliferation, adhesion, migration and differentiation of bone marrow mesenchymal stem cells(BMSCs). These findings indicate that nBM can be used as a potential osteoinductive active nanomaterial to enhance bone tissue engineering scaffolds with certain application prospects.